UPAYA PENINGKATAN KREATVITAS GURU DALAM MENGAJAR MELALUI SUPERVISI AKADEMIK DENGAN TEKNIK DEMONSTRATION TEACHING - Harsini, Widyan (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
Learning that occurs at SDN Kembangarum 01 Semarang City is still not able to maximize student learning. This is because at that time teachers still used traditional learning patterns or only relied on lectures and questions and answers (teacher centered) and were rigid without any form of creativity from the teacher to create learning innovations with their creativity. Some teachers are still teaching, especially in this pandemic era, do not use various media that can increase student creativity, students are only given assignments without being kept secret to better understand the material. The creativity of teaching teachers is usually still very minimal, teachers who are asked to show their ability to understand and explain teaching materials 70% do not understand teaching materials, while only 30% understand and explain teaching materials. So the implementation of learning at SDN Kembangarum 01 Semarang City is expected to provide intensive, inventive, creative, varied, and encouraging teaching. This study is intended to answer the question of whether academic supervision with demonstration teaching techniques can increase teacher creativity in teaching at SDN Kembangarum 01 Semarang City in the 2020/2021 Academic Year? These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that academic supervision with demonstration teaching techniques can increase teacher creativity in teaching at SDN Kembangarum 01 Semarang City in the 2020/2021 Academic Year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there are 11 teachers or 74% and in the second cycle there were 14 teachers or 93%. These results indicate that these results are in line with expectations. An increase also occurred in teacher activity in participating in academic supervision with demonstration teaching techniques where in the first cycle there were 13 teachers or 80% and the second cycle there were 14 teachers or 93%. The increase is the implementation of academic supervision with demonstration teaching techniques to be one effective way for school principals in increasing teacher creativity in learning